Genes in immune pathways associated with abnormal white matter integrity in first-episode and treatment-naïve patients with schizophrenia. (6th February 2019) - Xiang, Bo; Wang, Qiang; Lei, Wei; Li, Mingli; Li, Yinfei; Zhao, Liansheng; Ma, Xiaohong; Wang, Yingcheng; Yu, Hua; Li, Xiaojing; Meng, Yajing; Guo, Wanjun; et al.
Abstract : Background: Previous studies have inferred a strong genetic component in schizophrenia. However, the genetic variants involved in the susceptibility to schizophrenia remain unclear. Aims: To detect potential gene pathways and networks associated with schizophrenia, and to explore the relationship between common and rare variants in these pathways and abnormal white matter integrity in schizophrenia. Method: The analysis included 100 first-episode treatment-naïve patients with schizophrenia and 140 healthy controls. A network-based analysis was carried out on the data collected from the Psychiatric Genomics Consortium Phase I (PGC-I). Based on our genome-wide association study and whole-exome sequencing data-sets, we performed a gene-set analysis to detect associations between the combining effects of common and rare genetic variants and abnormal white matter integrity in schizophrenia. Results: Patients had significantly reduced functional anisotropy in the left and right anterior cingulate cortex, left and right precuneus and extra-nuclear ( t = 4.61–5.10, P FDR < 0.01), compared with controls. Generated from co-expression network analysis of the PGC-1 summary statistics of schizophrenia, a subnetwork of 207 genes associated with schizophrenia was identified ( P < 0.01), and 176 genes were co-expressed in four gene modules. Functional enrichment analysis for genes in each module revealed that the yellow module was enriched with highly co-expressed, innate immune response genes. Furthermore, rare variants of enriched genes in the yellow module were associated with reduced functional anisotropy in the left anterior cingulate cortex ( P = 0.006; P adjusted = 0.024) in patients only. Conclusions: The pathogenesis of schizophrenia may be substantially influenced by genes involved in the immune system, via both pathway and network. Declaration of interests: None.